Asymptotic Stability of Implicit Differential Systems in the Vicinity of Program Manifold - Zhumatov, S. S. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
Sufficient conditions for the asymptotic and uniform asymptotic stability of implicit differential systems in a neighborhood of the program manifold are established. Sufficient conditions of stability are also obtained for the known first integrals. A class of implicit systems for which it is possible to find the derivative of the Lyapunov function is selected.